Dakwah Islam Populer dan Taar`uf di Kalangan Anak Muda Muslim Urban - Akhmad Ramidi (Ulul Albab: Journal Da`wah and Social Religiosity, 2024)
One of the religious phenomena that has strengthened in the portrait of Islam in Indonesia is the emergence of the da'wah movement that voices the discourse of taaruf and piety among young urban Muslims. Inevitably, the emergence of this discourse as one of the counters to the narrative of promiscuity, one of which is the culture of dating. Although by definition taaruf and courtship have the meaning of knowing each other, courtship has been considered "bad" in the process of approaching between men and women towards marriage. Moreover, until now, the practice of dating among young people still leaves problems, one of which is getting pregnant outside of marriage. This study uses a qualitative research method with an ethnographic approach conducted for one year (February, 2020-December, 2021) to explore how young people's feedback and the dissemination of taaruf discourse among urban Muslim youth so that this Islamic da'wah movement is popular. Data collection is carried out through observation, interviews and documentation. This article argues that the popularity of Rumah TaarufQu as an Islamic matchmaking agency cannot be separated from the dexterity of packaging taaruf discourse and piety in young people's pop culture through social media so that it becomes a popular Islamic da'wah movement, in turn giving birth to the practice of young marriage among young people. In addition, Rumah TaarufQu also shows an accommodating attitude towards the association of today's young people so that it can be widely accepted.